2020
DOI: 10.3201/eid2607.200718
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic and Human-to-Human Transmission of SARS-CoV-2 in a 2-Family Cluster, Xuzhou, China

Abstract: His research interests include molecular epidemiologic studies on viral and bacterial diseases. References 1. World Health Organization. Statement on the second meeting of the International Health Regulations (2005) Emergency Committee regarding the outbreak of novel coronavirus (2019-nCoV) [cited 2020 Feb 18]. https://www.who.int/news-room/detail/30-01-2020statement-on-the-second-meeting-of-the-internationalhealth-regulations-(2005)-emergency-committee-regardingthe-outbreak-of-novel-coronavirus-(2019-ncov) 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
159
1
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(178 citation statements)
references
References 7 publications
(8 reference statements)
8
159
1
10
Order By: Relevance
“…Ultimately, an optimal view is asymptomatic cases may account for 60% of infections. However, recent research and case reports have confirmed that asymptomatic or pre-symptomatic cases can shed enough quantify of virus to be infectious [5][6][7][8]10]. Furthermore, if the infectivity of asymptomatic cases is similar to that of symptomatic cases, a faster epidemic will occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, an optimal view is asymptomatic cases may account for 60% of infections. However, recent research and case reports have confirmed that asymptomatic or pre-symptomatic cases can shed enough quantify of virus to be infectious [5][6][7][8]10]. Furthermore, if the infectivity of asymptomatic cases is similar to that of symptomatic cases, a faster epidemic will occur.…”
Section: Discussionmentioning
confidence: 99%
“…Two important factors may contribute a second wave of epidemic. First, unlike the 2003 SARS epidemic in which mainly symptomatic cases are infectious [4], asymptomatic infection of the SARS-CoV2 can transmit disease [5][6][7][8][9]. Studies have detected virus shedding in nasopharyngeal swap samples among asymptomatic cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we inoculated young and aged cynomolgus macaques with a low passage clinical isolate of SARS-CoV-2, which resulted in productive infection in the absence of overt clinical signs. Recent studies in human cases have shown that presymptomatic and asymptomatic cases can also shed virus (14,15). Increased age did not affect disease outcome, but there was prolonged viral shedding in the upper respiratory tract of aged animals.…”
mentioning
confidence: 89%
“…In view of the simulation by mathematical model, the initial number of the susceptible cases might be difficult to be determined. This might be demonstrated by the report that 60% of active cases might have no symptoms but could infect other healthy people [17][18][19]. And it is reported that the infected cases are of strong infection when they appeared to have no symptoms [24].…”
Section: 2mentioning
confidence: 96%
“…Similar to the simulation in China, the increase rate in simulation is not as large as that in the actual data. As it has been reported that the susceptible cases might be very inexplicit [17][18][19], the initial number of the susceptible cases S(t 0 ) is not accurate. It would be shown in the section of discussion.…”
mentioning
confidence: 99%